Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for pseudomyxoma peritonei of appendicular and extra-appendicular origin. Issue 6 (7th February 2018) - Delhorme, J-B; Severac, F; Averous, G; Glehen, O; Passot, G; Bakrin, N; Marchal, F; Pocard, M; Lo Dico, R; Eveno, C; Carrere, S; Sgarbura, O; et al.
Abstract: Background: The prognostic value of the primary neoplasm responsible for pseudomyxoma peritonei (PMP) remains poorly studied. The aim of this study was to determine the prognosis for patients with extra-appendicular PMP (EA-PMP) treated optimally with complete cytoreductive surgery (CCRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Methods: All patients treated for PMP with CCRS and HIPEC between 1994 and 2016 were selected retrospectively from a French multicentre database. Patients with EA-PMP had pathologically confirmed non-neoplastic appendices and were matched in a 1 : 4 ratio with patients treated for appendicular PMP (A-PMP), based on a propensity score. Results: Some 726 patients were identified, of which 61 (EA-PMP group) were matched with 244 patients (A-PMP group). The origins of primary tumours in the EA-PMP group included the ovary (45 patients), colon (4), urachus (4), small bowel (1), pancreas (1) and unknown (6). The median peritoneal carcinomatosis index was comparable in EA-PMP and A-PMP groups (15·5 versus 18 respectively; P = 0·315). In-hospital mortality (3 versus 2·9 per cent; P = 1·000) and major morbidity 26 versus 25·0 per cent; P = 0·869) were also similar between the two groups. Median follow-up was 66·9 months. The 5-year overall survival rate was 87·8 (95 per cent c.i. 83·2 to 92·5) per cent in the A-PMP group and 87 (77 to 96) per cent in the EA-PMP group. The 5-year disease-free survival rate was 66·0 (58·7 to 73·4) per cent and 70 (53 to 83) per cent respectively. Conclusion: Overall and disease-free survival following treatment with CCRS and HIPEC is similar in patients with pseudomyxoma peritonei of appendicular or extra-appendicular origin. Abstract : Survival similar